2019
DOI: 10.18034/abcjar.v8i1.83
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of Malt Barley (Hordeum Vulgare L.) Varieties in the highlands of North Gondar

Abstract: Study was initiated with the objectives to identify high yielder malt barley varieties. The trial has been conducted during 2014 main season and laid out on randomized complete block design with three replications. Analysis of variance was computed using SAS, 2002. At Dabat, result showed that highly significant difference among the varieties (p < 0.05) for all agronomic traits. At Debark and Wegera the analysis of variance indicated that highly significant to a significant difference among varieties  at p … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Previous studies by Molla et al [18] and Bizuneh & Assefa [28] reported variations between genotypes for grain yield, time of germination, flowering and maturity, plant height, spike length, and the number of tillers. Similarly, significant differences were recorded for agronomic traits and grain yield [31]. In other studies, there was also a significant difference in malt barley variety for tillering capacity [32].…”
Section: E Effect Of Malt Barley Variety On Yield and Yieldmentioning
confidence: 53%
“…Previous studies by Molla et al [18] and Bizuneh & Assefa [28] reported variations between genotypes for grain yield, time of germination, flowering and maturity, plant height, spike length, and the number of tillers. Similarly, significant differences were recorded for agronomic traits and grain yield [31]. In other studies, there was also a significant difference in malt barley variety for tillering capacity [32].…”
Section: E Effect Of Malt Barley Variety On Yield and Yieldmentioning
confidence: 53%
“…Likewise, [19,28] reported variations between genotypes for grain yield, time of germination, flowering and maturity, plant height, spike length, and the number of tillers. Similarly, significant differences were recorded for agronomic traits and grain yield [48]. In other studies, there was also a significant difference in malt barley variety for tillering capacity [1].…”
Section: Main Effects Of Malt Barley Varieties On Selected Parametersmentioning
confidence: 59%